A STUDY OF CULTURAL DIVERSITY BASED ON AFRICAN, AFRO-BRAZILIAN AND INDIGENOUS ARTS IN PRIMARY EDUCATION - do Socorro das Neves Barbosa, Jakelyane; Jacson da Silva Carneiro de Oliveira, Rafael; de Oliveira Cruz, Otemar; Vieira Nojosa , Natalina; Amorim de Souza, Michele; Valéria Miranda Delarolli, Adriana (Revista Gênero e Interdisciplinaridade, 2023)
The premise of this research is to encourage discussions about the importance of approaching cultural diversity, emphasizing African, Afro-Brazilian and indigenous arts in art classes in the context of basic education, through the construction of reflections that allow the appreciation and recognition of these cultures. as makers of Brazilian cultural identity. This is a bibliographical research, having as its main theoretical body, authors and articles that talk about the subject, as well as legislation that deals with the subject. Based on this research, it is possible to engender reflections about the rich elements that constitute African, Afro-Brazilian and indigenous cultures to disseminate them as belonging to Brazilian culture, as well as the implicit art in these cultures and their relationship with the educational field. With this, the reflection intends to help basic education teachers who feel challenged to significantly approach the theme, with the respect and appreciation that are due to them inside and outside the school.